2006
DOI: 10.1111/j.0066-4812.2006.00590.x
|View full text |Cite
|
Sign up to set email alerts
|

Maria's Burden: Contract Cleaning and the Crisis of Social Reproduction in Post‐apartheid South Africa

Abstract: The life of Maria Dlamini, a contract cleaner at the University of the Witwatersrand, is used to explore continuities and discontinuities between the apartheid labour regime and the neoliberal, post-apartheid order in South Africa. As South African institutions have adopted neoliberal market strategies, the growth in the contracting-out of cleaning has intensified work and reduced wages and benefits for many workers. Significantly, as was the case with the migrant labor system under apartheid, it has also incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 14 publications
1
7
0
2
Order By: Relevance
“…Ryan and Herod (2006) report that some firms in Australasia have been willing to make a loss on their contracts if they are able to recoup a small profit from the ‘special services’ they sell to the client or through the sub‐subcontracting of work. Moreover, in a labour‐intensive industry, wages and conditions are the easiest place to make savings, and cleaners have often suffered reductions in pay (see Aguiar, 2006; Bezuidenhout and Fakier, 2006). 4 In addition, subcontracting is also associated with a sharp intensification of work.…”
Section: Neoliberalism's Challenge To Cleaning Cleaners and Trade Unmentioning
confidence: 99%
“…Ryan and Herod (2006) report that some firms in Australasia have been willing to make a loss on their contracts if they are able to recoup a small profit from the ‘special services’ they sell to the client or through the sub‐subcontracting of work. Moreover, in a labour‐intensive industry, wages and conditions are the easiest place to make savings, and cleaners have often suffered reductions in pay (see Aguiar, 2006; Bezuidenhout and Fakier, 2006). 4 In addition, subcontracting is also associated with a sharp intensification of work.…”
Section: Neoliberalism's Challenge To Cleaning Cleaners and Trade Unmentioning
confidence: 99%
“…As Russell (2003) notes, these forms of familial support are outcomes of changing African family structures in the context of new economic demands. Research by Bezuidenhout and Fakier (2006) reveals how the wages of a single cleaner at a university were used to support 21 family members across urban and rural space. Research among youth in the Cape Town area has also found that it is overwhelmingly young black adults who report "many prospective obligations to diverse kin, including more distant kin" (Harper and Seekings, 2010, p. 1).…”
Section: The Race For Class: Education During and After Apartheidmentioning
confidence: 99%
“…O status associado a esse tipo de atividade é um elemento central na formação e na percepção da dignidade do trabalho e, no caso do serviço de limpeza, invoca vários tipos de preconceito (Bolton, 2007). Observa-se, assim, que para o imaginário coletivo, o trabalho de limpeza é considerado feminino, não qualificado e subalterno, relembrando ou reproduzindo socialmente o servilismo do período escravista (Bezuidenhout & Fakier, 2006). Essa herança tem impactos diretos no significado do trabalho e, consequentemente, na construção da identidade social dos trabalhadores (Diogo & Maheirie, 2007).…”
Section: Significado Cultural Ou Interpessoalunclassified
“…No estudo 2, verificou-se que a forma como a profissão de auxiliar de serviços gerais é percebida na sociedade impacta na rotatividade. A hipótese para a maior participação masculina no índice de rotatividade da função de servente de limpeza é a representação de gênero que permeia o imaginário social, no qual as atividades de limpeza são consideradas femininas (Bezuidenhout & Fakier, 2006). Apesar da validade da hipótese, fatores como falta de reconhecimento, desprezo e invisibilidade social da profissão levam os funcionários a buscarem alternativas no mercado, dando suporte a hipótese geral desta pesquisa.…”
Section: Discussão Geralunclassified